2006
DOI: 10.1038/sj.bjp.0706553
|View full text |Cite
|
Sign up to set email alerts
|

G‐protein‐coupled receptor dephosphorylation at the cell surface

Abstract: Abbreviations: GPCR, G-protein-coupled receptor; GRK, G-protein-coupled receptor kinase; PKA, protein kinase A; PKC, protein kinase C Agonist-induced desensitization of G-protein-coupled receptors (GPCRs) usually involves phosphorylation of the receptor by G-protein-coupled receptor kinases (GRKs) or second messenger-dependent protein kinases such as PKC and PKA. Phosphorylation by GRKs promotes arrestin binding to the receptor, which not only uncouples receptor and G protein but also targets the receptor to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…There has been some controversy about the possibility of plasma membrane dephosphorylation of the GRK phosphorylated receptor and the recycling of the phosphorylated receptor [30] , [34] , [49] – [51] . Recently we have shown that (i) β2AR can be dephosphorylated when internalization is blocked with either hypertonic sucrose treatment or through the use of a dominant negative form of dynamin [30] , and (ii) that dephosphorylation occurs with no detectable internalization [16] .…”
Section: Resultsmentioning
confidence: 99%
“…There has been some controversy about the possibility of plasma membrane dephosphorylation of the GRK phosphorylated receptor and the recycling of the phosphorylated receptor [30] , [34] , [49] – [51] . Recently we have shown that (i) β2AR can be dephosphorylated when internalization is blocked with either hypertonic sucrose treatment or through the use of a dominant negative form of dynamin [30] , and (ii) that dephosphorylation occurs with no detectable internalization [16] .…”
Section: Resultsmentioning
confidence: 99%
“…Although our prior study showed that PKA and possibly GRK site dephosphorylations occurred at the plasma membrane, several important questions remained (Kelly, 2006). First, to what extent does functional resensitization of agonist stimulation of the ␤ 2 AR and adenylyl cyclase correlate with the rate constants for dephosphorylation of the PKA and GRK sites?…”
mentioning
confidence: 97%
“…During the desensitization process, G-protein-coupled receptor kinase (GRK) phosphorylated GPCRs undergo clathrin-mediated endocytosis as a result of β-arrestin-binding. It was initially hypothesized for endosomal recycling receptors, with the β2-adrenergic receptor (β2AR) serving as a role model for other GPCRs, that a downstream dephosphorylation/resensitization step was either initiated or accompanied by an acidic-induced loss of ligand binding. This view, however, was broadened to include the discovery that resensitization relevant phosphatases are active in nonendosomal cell compartments including those at the plasma membrane. Thus, β-arrestin-based receptor trafficking information appears susceptible to modification even before the receptor has an opportunity to internalize from the plasma membrane, and to assess it requires measurement techniques applicable over both short and long times. In addition, if we use the beta2-adrenergic receptor (β2AR) and rhodopsin as templates for characterizing the GHSR1a, then the principal locations to assess trafficking information are in its C-tail and ICL2 (Figure b–e). ,, Generation of a GHSR1/arrestin active space-filling model (Figure c, lower panels) by corresponding residue substitution of its ICL2 into the rhodopsin ICL2 (Figure c, upper panels) suggests conservation of the ability to bind the active arrestin cleft as well as demonstrating conservation of a short N-capped proline α helix (Figure a, rhodopsin; Figure d, GHSR1a) within 2.4 Å of a hydrophobic patch containing arrestin leucine 250 (Figure e.…”
Section: Resultsmentioning
confidence: 99%